CONSIDERAÇÕES SOBRE A JUDICIALIZAÇÃO DA ASSISTÊNCIA FARMACÊUTICA NA COMARCA DE PONTA GROSSA-PR NO ANO DE 2011 - Blood, Renata Luciane Polsaque Young (2013)
The 1988 Federal Constitution the legal innovates with rising health category of the social right. This same law stipulates that the realization of this right must be done through the implementation of social and economic policies with a focus on community. With positivization the right to health and public policy of the Judiciary shall be entitled to enjoy the benefits of demands aimed at public health services. Therefore, the legalization of political relations is an inevitable consequence, since it is aimed at a body of positive law and state institutions. In this context, the intervention of the legal system in the politics of pharmaceutical care has been the subject of much criticism, mainly by disregarding the internal elements of this policy, by privileging the satisfaction of individual interests and not open to dialogue with other stakeholders in the process. In order to see how the legal system in the District of Ponta Grossa - PR, in 2011, guaranteed the right to social assistance drug,this study drew on the quantitative and qualitative methodologies. So, at first was performed to characterize the objective processes, and soon after applied to qualitative methodology of the Collective Subject Discourse, where it was possible to identify the main arguments used by the judges in assessing the lawsuits with claims for drugs.